Mediating Effect of Self-Efficacy on Self-Leadership and Teachers’ Organizational Citizenship Behavior: A Conceptual Framework - Mansor, Ainimazita; Darus, Amer; Dali, Mohd Hasani (International Journal of Economics, Business and Management Studies, 2013)
If one assumes that organizational citizenship behavior (OCBs) have an effect on organizational performance; it makes sense to identify those variables that increase these behaviors in organizational setting. That is probably why most research in this domain has focused on the potential antecedents of OCBs. One of the main reasons for the interest in OCBs is that they are expected to be positively related to measures of organizational effectiveness. The challenges in meeting the demand for highly qualified teachers are essential. Therefore, the purpose of this paper is to determine in what level the teachers at primary schools display contextual performance namely OCB. This paper will also examine the influence of self-leadership and self-efficacy (individual-level variables) and OCB (individual-level performance) according to the perceptions of the teacher itself.